PENGARUH NET PROFIT MARGIN, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP PERUBAHAN LABA PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Tahun 2013 – 2018) - Saraswati Dewi; alean kistiani; yunita niqrisah (Universitas Boyolali, 2020)
Every company has a desire to make a profit in every production. In addition, the wider community measures the success of the company based on the company's ability to earn profits seen from the company's performance, but not only that the success of a company is also seen from the achievement of the company's vision and mission goals. One alternative to find out the financial information generated is useful by predicting changes in earnings. Including financial conditions in the future is analyzing financial ratios. This study aims to determine the effect of Net Profit Margin, Return On Assets and Return On Equity on changes in company profits in food and beverage Sub Sector Companies Listed on the Indonesia Stock Exchange Period 2013 - 2018. The type of data used is secondary data, namely regarding financial statements. The sampling technique used was purposive sampling of 13 companies. All data were analyzed by multiple linear regression analysis, classic assumption test, t test and coefficient of determination. The results of the research show partially the variables that influence the change in company profits are only Net Profit Margin. And simultaneously the independent variable has no effect on the dependent variable. Keywords: Net Profit Margin, Return On Asset, Return On Equity, changes in company profits.